The Significance of Integrating Critical Thinking Perspectives in EFL Programs - Mzeil , Ahmad H. (Journal of Ecohumanism, 2024)
Various comprehensive language education programs have been employed by educational institutions to advance their curricula in teaching English as a foreign language (EFL). However, the focus of most of these EFL programs was to improve students’ vocabulary and grammar without improving their awareness of the English language. The focus was on rote learning which depends on the memorization of rules and vocabulary without using the target language effectively. With conservation learning, students, as well as instructors, have been exposed to looking at the target language critically and how this language functions effectively within social, cultural, and ideological contexts. This study investigates the thoughts on integrating critical approaches, critical language awareness (CLA), and critical discourse analysis (CDA) into EFL programs to equip students with cognitive and analytical to communicate in the target language effectively. In this study, 20 participants from a higher education institution consented to conduct a semi-structured interview to measure the students’ inclination to include critical thinking courses in English language teaching. It has been shown that most students believe in the importance of critical thinking courses to be familiar with contextual awareness, assumption analysis, and imaginative speculation.